World food security : a history since 1945 - Shaw, D. John. (Basingstoke [England] ; New York : Palgrave Macmillan, 2007)
A comprehensive account of the numerous attempts made since the Seco nd World War to provide food security for all, this title provides a re ference source for all those involved and interested in food security i ssues.
pt. I. 1945-70. Early attempts : FAO's pioneering work. FAO's origin s ; Food surpluses : historical background ; World Food Board proposal ; International Commodity Clearing House ; A world food reserve ; Natio nal food reserves in developing countries ; International commodity agr eements ; Freedom from Hunger campaign ; The development of food aid -- pt. II. 1970-90. The world food crisis of the 1970s and its aftermath. World food crisis ; World Food Conference, 1974 ; International Undert aking on World Food Security ; An international grain reserves system ; International Emergency Food Reserve ; Global information and early wa rning system ; International Trade, Stability and Agricultural Adjustme nt ; World Food Council ; ILO World Employment Conference, 1976 ; Food entitlement ; Pragmatism and politics ; World Bank perspective ; Food s ubsidies -- pt. III. The 1990s and beyond : international conferences. International development strategy for the 1990s ; International confer ences ; World Summit for Children, 1990 ; UN Conference on Environment and Development, 1992 ; International Conference on Water and the Envir onment, 1992 ; International Conference on Nutrition, 1992 ; World Conf erence on Human Rights, 1993 ; World Conference on Overcoming Global Hu nger, 1993 ; International Conference on Population and Development, 19 94 ; World Summit for Social Development, 1995 ; A 2020 Vision for Food , Agriculture and the Environment, 1995 ; Fourth World Conference on Wo men, 1995 ; World Food Summit, 1996 ; World Agricultural Trade : WTO an d the Doha Declaration ; UN Millennium Summit, 2000 ; International Con ference on Financing for Development, 2002 ; World Summit, 2005 -- pt. IV. Assessment : the graveyard of aspirations. Redefining the concept o f food security ; Dimensions of poverty ; Future action.
Includes bibliographical references (p. 462-495) and index.
Keywords: Food supply -- History; Food relief -- International cooperation -- History; Agricultural assistance -- History; Hunger -- Prevention -- History